Verb Learning in 14- and 18-Month-Old English-Learning Infants. Issue 3 (3rd July 2017) - He, Angela Xiaoxue; Lidz, Jeffrey
ABSTRACT: The present study investigates English-learning infants' early understanding of the link between the grammatical category verb and the conceptual category event, and their ability to recruit morphosyntactic information online to learn novel verb meanings. We report two experiments using an infant-controlled Habituation-Switch Paradigm. In Experiment 1, we habituated 14- and 18-month-old infants with two scenes each labeled by a novel intransitive verb embedded in the frame "is ___ing": a penguin-spinning scene paired with "it's dok ing", a penguin-cartwheeling scene paired with "it's pratch ing". At test, infants in both age groups dishabituated when the scene-sentence pairings got switched (e.g., penguin-spinning—"it's pratch ing"). This finding is consistent with two explanations: (1) infants were able to link verbs to event concepts (as opposed to other concepts, e.g., objects) and (2) infants were simply tracking the surface-level mapping between scenes and sentences, and it was scene-sentence mismatch that elicited dishabituation, not their knowledge of verb-event link. In Experiment 2, we investigated these two possibilities, and found that 14-month-olds were sensitive to any type of mismatch, whereas 18-month-olds dishabituated only to a mismatch that involved a change in word meaning . Together, these results provide evidence that 18-month-old English-learning infants are able to learn novel verbs by recruiting morphosyntactic cues for verb categorization and use the verb-event link to constrain their search space of possible verb meanings.